Introducing human resource management - Foot, Margaret; Hook, Caroline (Essex, England ; New York : Financial Times Prentice Hall, 2005)
The book explores the latest developments in areas such as employment law and strategic HR as well as current applications of HR practice in the workplace.
Includes bibliographical references and indexes.
rua 27/02/15
Loans
Keywords: Personnel management; Employee rights; Human resource management; Human management